An Update of Armamentarium for Non Invasive Cardiac Haemodynamics and Congestion Evaluation for Acute Heart Failure Patients - Salvatore Di Somma (Universitas Brawijaya, 2021)
In the management of Acute Heart Failure(AHF) patients ,current guidelines suggest to make a prompt clinical assessments that include patient’s congestion and perfusion status evaluation, in order to start appropriate treatments. Unfortunately ,so far, an accurate evaluation of haemodynamic and fluid status of AHF patients is only possible using invasive methods ;conseguently there is an unmeet need for noninvasive technologies to easly detect different phenotypes of AHF subjects based on different cardiac haemodynamic profiles . Technological advances such as: Biva,Nexfin or NICas could allow for routine noninvasive continuous monitoring of Cardiac Hemodymanics and Fluid content in Acute Heart Failure patients. These non invasive measurements may provide important information for improving diagnosis, developing individualized therapeutic management plans/disposition decisions and predicting short term mortality